LOCAL INHABITANS AS PART OF NAZI PUNITIVE BODIES ON THE TERRITORY OF KHARKIV REGION (1941–1943) (Південний архів (історичні науки), 2023)
The purpose of this study is to examine the participation of local inhabitants in auxiliary formations of Nazi punitive bodies operated on the territory of Kharkiv region during 1941–1943. Furthermore, the problem of collaborators involved in the commission of war crimes is raised. The methodological base consists of general scientific methods (analysis, synthesis, deduction, induction, systematic approach) along with special historical ones (historical-comparative, historical-systematic). The principles of scientific, objectivity, historicism are also applied. Results of research. From the very first days of the World War II the Wehrmacht and later police structures of RSHA (Reichssicherheitshauptamt) faced with severe staff shortages. In order to complete military-police units operated on the occupied Soviet territories local collaborators were widely involved. The main source of staffing for Ukrainian auxiliary units of Wehrmacht and Police in Kharkiv region became Soviet prisoners of war – Ukrainians and Russians by nationality who lived on the territories of UkSSR and RSFSR before the war as well as local residents from civilian population. The materials are based on the analysis of archival criminal cases of collaborators – former members of GFP 560 (Geheime Feldpolizei), Security Police (Sicherheitspolizei/ SiPo) and SD who served in “Kharkiv General District” (Generalbezirk Charkiw). The article is devoted to a close analysis of completing and functioning of auxiliary units staffed by Soviet citizens in the structure of Nazi military police institutions that operated on the territory of Kharkiv region during 1941–1943. Furthermore, the participation of such units in committing war crimes is revealed. Conclusions. The main reason why local residents collaborated with German occupation authorities was Stalin’s punitive-repressive policy aiming to establish Soviet variant of totalitarianism. Significant role in disillusionment with the Bolshevik regime played catastrophic defeats of the Red Army at the outbreak of German-Soviet war. Local people were politically disoriented because of communist propaganda and became victims abandoned to the mercy of an infuriated enemy without a livelihood. Hundreds of thousands of captured Red Army soldiers found themselves on the verge of survival. However, another important factor that made local inhabitants collaborate with Nazis was ruthless occupation regime. Local people served in Nazi punitive bodies but such kind of cooperation wasn’t on a voluntary basis but was performed under the pressure of German government. Collaboration with occupation authorities didn’t have any certain ideological convictions but was mainly caused by basic human desire just to stay alive in highly complex situations and adapt to fierce conditions of “new order”. However, we should keep in mind that collaborators were not only mainstay for the German occupation regime but they also became diligent performers and accomplices of Nazi bloody crimes in Kharkiv region.
Keywords: military collaboration, Nazi war crimes, Security Police (SiPo) and SD, Secret Field Police (GFP), Ukrainian Auxiliary Police, Kharkiv region